Proses masuknya agama islam di asia tenggara - Razaq, Muhammad Akbar (Maliki Interdisciplinary Journal, 2026)
EIslamic civilization is one of the major civilizations in human history, having a wide influejjnce on the development of science, politics, economics, and world culture. Since the time of Prophet Muhammad SAW, Islam has rapidly expanded from the Arabian Peninsula to Asia, Africa, and Europe. One example of this is the Islamic civilization that developed in Southeast Asia. The arrival of Islam in Southeast Asia was different from that in other regions, which was predominantly carried out through military conquest; instead, Islam entered Southeast Asia through peaceful means. Regarding the spread of Islam in Southeast Asia, many scholars have proposed various theories about how Islam first arrived in the region